An Essay on the Bonifacio-Aguinaldo Schism as Manifestation of National Disunity - Viray, Joseph Reylan; Viray, Kriztine (Social Sciences and Development Review, 2024)
This essay conducts an analysis of the underlying factors contributing to theideological and strategic disagreement between Emilio Aguinaldo and AndresBonifacio during the Philippine Revolution. Employing a multi-dimensional approach, the essay scrutinizes the distinct objectives each leader had for the revolution, highlighting the complexities of their conflicting perspectives. Likewise it evaluates the substantive impact of the Aguinaldo-Bonifacio schism on what was otherwise considered a unified revolutionary movement, thereby presenting implications for the interpretation of historical revolutions.
Keywords: Bonifacio; nation; nationhood; Aguinaldo; Philippine Revolution; Philippine Studies